Hypoalbuminemia predicts the outcome of COVID‐19 independent of age and co‐morbidity - Huang, Jiaofeng; Cheng, Aiguo; Kumar, Rahul; Fang, Yingying; Chen, Gongping; Zhu, Yueyong; Lin, Su (Journal of medical virology, 2020)
The coronavirus disease 2019 (COVID‐19) has evolved into a pandemic rapidly. Most of the literature show that the elevated liver enzymes in COVID‐19 are of little clinical significance. Lower albumin level is seen in severe COVID‐19 and is not parallel to the changes in alanine aminotransferase and aspartate aminotransferase levels. We aimed to explore the impact of hypoalbuminemia in COVID‐19. This retrospective cohort study included adult patients with confirmed COVID‐19. The relationship between hypoalbuminemia and death was studied using binary logistic analysis. A total of 299 adult patients were included, 160 (53.5%) were males and the average age was 53.4 ± 16.7 years. The median time from the onset of illness to admission was 3 days (interquartile ranges, 2‐5). Approximately one‐third of the patients had comorbidities. Hypoalbuminemia (<35 g/L) was found in 106 (35.5%) patients. The difference in albumin was considerable between survivors and non‐survivors (37.6 ± 6.2 vs 30.5 ± 4.0, P < .001). Serum albumin level was inversely correlated to white blood cell (r = –.149, P = .01) and neutrophil to lymphocyte ratio (r = −.298, P < .001). Multivariate analysis showed the presence of comorbidities (OR, 6.816; 95% CI, 1.361‐34.133), lymphopenia (OR, 13.130; 95% CI, 1.632‐105.658) and hypoalbuminemia (OR, 6.394; 95% CI, 1.315‐31.092) were independent predictive factors for mortality. In conclusion, hypoalbuminemia is associated with the outcome of COVID‐19. The potential therapeutic value of albumin infusion in COVID‐19 should be further explored at the earliest.